Event-Triggered and Time-Triggered Control Paradigms - Obermaisser, Roman (Real-Time Systems Series,, 2005)
Event-Triggered and Time-Triggered Control Paradigms presents a valuable survey about existing architectures for safety-critical applications and discusses the issues that must be considered when moving from a federated to an integrated architecture. The book focuses on one key topic--the amalgamation of the event-triggered and the time-triggered control paradigm into a coherent integrated architecture. The architecture provides for the integration of independent distributed application subsystems by introducing multi-criticality nodes and virtual networks of known temporal properties.